(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The National Council of Educational Research and Training(NCERT) is the apex body for curriculum related matters for school education inIndia. The NCERT provides support and technical assistance to a number ofschools in India and oversees manyaspects of enforcement of education policies. In India, the various curriculumbodies governing school education system are: The state government boards, in which the majority ofIndian children are enrolled. The Central Board of SecondaryEducation (CBSE). CBSE conducts two examinations, namely, the All IndiaSecondary School Examination, AISSE (Class/Grade 10) and the All India SeniorSchool Certificate Examination, AISSCE (Class/Grade 12). The Council for the Indian SchoolCertificate Examinations (CISCE). CISCE conducts three examinations, namely,the Indian Certificate of Secondary Education (ICSE - Class/ Grade 10); TheIndian School Certificate (ISC - Class/ Grade 12) and the Certificate inVocational Education (CVE - Class/Grade 12).